Signaling principles in interactive learning media through expert's walkthrough - Derlina, Derlina; Dalle, Juhriyansyah; Hadi, Sutarto; Abdul Mutalib, Ariffin; Sumantri, Candra (Anadolu University, 2018)
This study analyzes the impact of signaling principles upon the effective use of interactive learning media. Normally, designers just design and develop learning media for use in schools without considering the way it eases users’ tasks. Bearing in mind that signaling users while they are learning through interactive learning media is important, this study incorporates signaling principles while designing it. Thus, this paper aims to discuss the appropriate signaling principles for learning media from experts’ perspective. The Iterative Triangulation Methodology was applied to achieve the aim. Altogether, activities were carried out in three phases: requirement analysis, design and development of the prototype, and expert evaluation using a walkthrough. Results revealed that although the prototype was designed by involving users, experts still discovered a number of flaws in the exercises as a result of not properly applying the signaling principles.